2021
DOI: 10.1177/11206721211014380
|View full text |Cite
|
Sign up to set email alerts
|

Rebubbling rate in preloaded versus surgeon prepared DSAEK

Abstract: Purpose: To compare the clinical outcomes of eye bank preloaded Descemet stripping automated endothelial keratoplasty (DSAEK) grafts and surgeon prepared. Methods: In this retrospective study, the data were obtained from two groups (a) surgeon cut DSAEK where tissue was prepared by the surgeon immediately before surgery, and (b) preloaded DSAEK tissue shipped to the surgeon after preparation by the eye bank. Standard DSAEK preparations using Moria microkeratome with single pass method were performed. For the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
3
1
0
Order By: Relevance
“…Romano et al looked at DMEK graft preparation and found signi cantly higher adhesion and lower re-bubbling rates with surgeon prepared DMEK grafts compared to eye bank prepared tissue (18). Similar results were seen in a study examining re-bubbling rates in DSAEK procedures, with fewer detachments occurring in the surgeon prepared group (42). The use of surgeon or local technician prepared endothelial grafts, both DMEK and traditional DSAEK, have also been shown to signi cantly reduce surgical expenses in Canada and the United Kingdom (42,43).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Romano et al looked at DMEK graft preparation and found signi cantly higher adhesion and lower re-bubbling rates with surgeon prepared DMEK grafts compared to eye bank prepared tissue (18). Similar results were seen in a study examining re-bubbling rates in DSAEK procedures, with fewer detachments occurring in the surgeon prepared group (42). The use of surgeon or local technician prepared endothelial grafts, both DMEK and traditional DSAEK, have also been shown to signi cantly reduce surgical expenses in Canada and the United Kingdom (42,43).…”
Section: Discussionsupporting
confidence: 69%
“…Similar results were seen in a study examining re-bubbling rates in DSAEK procedures, with fewer detachments occurring in the surgeon prepared group (42). The use of surgeon or local technician prepared endothelial grafts, both DMEK and traditional DSAEK, have also been shown to signi cantly reduce surgical expenses in Canada and the United Kingdom (42,43). These studies did not speci cally analyse surgeon prepared UT-DSAEK grafts.…”
Section: Discussionsupporting
confidence: 57%
“…Similar results were seen in a study examining re-bubbling rates in DSAEK procedures, with fewer detachments occurring in the surgeon prepared group [42]. The use of surgeon or local technician prepared endothelial grafts, both DMEK and traditional DSAEK, have also been shown to significantly reduce surgical expenses in Canada and the United Kingdom [42,43]. These studies did not specifically analyse surgeon prepared UT-DSAEK grafts.…”
Section: Clinical Outcomessupporting
confidence: 52%
“…Romano et al looked at DMEK graft preparation and found significantly higher adhesion and lower re-bubbling rates with surgeon prepared DMEK grafts compared to eye bank prepared tissue [18]. Similar results were seen in a study examining re-bubbling rates in DSAEK procedures, with fewer detachments occurring in the surgeon prepared group [42]. The use of surgeon or local technician prepared endothelial grafts, both DMEK and traditional DSAEK, have also been shown to significantly reduce surgical expenses in Canada and the United Kingdom [42,43].…”
Section: Clinical Outcomesmentioning
confidence: 68%
“…[ 69 ] Nonetheless, this finding presents no practical implications for DSAEK, given that precut tissues provided similar visual and refractive outcomes, rebubbling rates, and endothelial cell loss after 12 months as non-precut tissues. [ 70 ]…”
Section: Methodsmentioning
confidence: 99%